Utilization Of Golden Snail Flour (GSF) on Ration of Quail - Vera Novita Sari Siahaan; T H Wahyuni; A.H.Daulay; S. R. Lubis (Talenta Publisher, 2020)
Feed is one of the critical factors for the success of livestock production because it contributes 70-80% of production costs. High protein feed ingredients are expensive, so it is necessary to use non conventional feed. Golden snail are pests that interfere to rice growth in agricultural areas, one of which is in North Tapanuli Regency. Golden snail have a high protein content so they are very efficient to use as a source of protein feed. In this study, golden snail in the form of flour was used as a substitute for fish meal in laying quail rations. The research used Completely Randomized Design (CRD) with 4 treatments, namely P0 = 8% fish meal, P1 = 4% GSF, P2 = 8% GSF, P3 = 12% GSF with 5 replications. The research parameters were feed consumption, egg production, egg weight, feed conversion and over feed cost income. The results showed a significant effect of P2 on egg production as much as 31.71% and income over feed cost IDR 2602.15/ head compare to other treatments of quail eggs. However, giving GSF did not show a significant effect on egg weight, feed consumption and ration conversion. The results showed that the use of GSF was suitable as a substitute for fish meal on quail feed an application of 8% GSF for quail feed was a novelty finding.